Coevolution between MHC Class I and Antigen-Processing Genes in Salamanders. (10th August 2021) - Palomar, Gemma; Dudek, Katarzyna; Migalska, Magdalena; Arntzen, J W; Ficetola, G Francesco; Jelić, Dušan; Jockusch, Elizabeth; Martínez-Solano, Inigo; Matsunami, Masatoshi; Shaffer, H Bradley; Vörös, Judit; Waldman, Bruce; et al.
Abstract: Proteins encoded by antigen-processing genes (APGs) provide major histocompatibility complex (MHC) class I (MHC-I) with antigenic peptides. In mammals, polymorphic multigenic MHC-I family is served by monomorphic APGs, whereas in certain nonmammalian species both MHC-I and APGs are polymorphic and coevolve within stable haplotypes. Coevolution was suggested as an ancestral gnathostome feature, presumably enabling only a single highly expressed classical MHC-I gene. In this view coevolution, while optimizing some aspects of adaptive immunity, would also limit its flexibility by preventing the expansion of classical MHC-I into a multigene family. However, some nonmammalian taxa, such as salamanders, have multiple highly expressed MHC-I genes, suggesting either that coevolution is relaxed or that it does not prevent the establishment of multigene MHC-I . To distinguish between these two alternatives, we use salamanders (30 species from 16 genera representing six families) to test, within a comparative framework, a major prediction of the coevolution hypothesis: the positive correlation between MHC-I and APG diversity. We found that MHC-I diversity explained both within-individual and species-wide diversity of two APGs, TAP1 and TAP2, supporting their coevolution with MHC-I, whereas no consistent effect was detected for the other three APGs ( PSMB8, PSMB9, and TAPBP ). Our results imply that although coevolution occurs in salamanders, it does not preclude the expansion of the MHC-I gene family. Contrary to the previous suggestions, nonmammalian vertebrates thus may be able to accommodate diverse selection pressures with flexibility granted by rapid expansion or contraction of the MHC-I family, while retaining the benefits of coevolution between MHC-I and TAPs .